Silicon tris(perchloro)dioxolene: a neutral triplet diradical - Maskey, Rezisha; Wadepohl, Hubert; Greb, Lutz (Angewandte Chemie. International edition, 2019)
The reaction of ortho-quinones with silicon tetraiodide leads to neutral silicon trisdioxolenes in high yield, delivering the unknown oxidized form of triscatecholatosilicate dianions and the first example of open-shell semiquinonates connected via a single non-metal center. Silicon tris(perchloro)dioxolene is a stable diradical with a triplet ground state, as supported by X-ray diffraction; IR, resonance Raman, UV/Vis, and (VT)EPR spectroscopy; and Kohn-Sham broken-symmetry computations. Preliminary results suggest that the preferred magnetic ground state can be altered through variation of the substituents.